2017
DOI: 10.1016/j.dhjo.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Live birth, miscarriage, and abortion among U.S. women with and without disabilities

Abstract: Background Prior studies have found that women with disabilities who give birth are more likely to have preterm deliveries and low birthweight infants. However, it is not known what proportion of pregnant women with disabilities experience live birth, versus miscarriage or abortion. Objective To compare proportions of live birth, miscarriage, and abortion among women with basic action difficulties, women with complex activity limitations, and women without disabilities in a nationally representative sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Of the 16 included studies, eight were cross‐sectional 13,14,19‐24 and eight were retrospective cohorts 15,17,25‐30 . Studies were conducted in the United States ( n = 13) 13,15,17,19‐22,25‐30 and the United Kingdom (UK) ( n = 3) 14,23,24 and based on nine different data sources including: Massachusetts Pregnancy to Early Life Longitudinal data system (PELL, n = 3) 25‐27 ; California birth certificate and hospital discharge records ( n = 3) 15,17,29 ; Pregnancy Risk Assessment Monitoring System (PRAMS, n = 3) 13,21,22 ; and the UK National Health Service Care Quality Commission Survey ( n = 2) 14,23 . Definitions of physical disabilities varied.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 included studies, eight were cross‐sectional 13,14,19‐24 and eight were retrospective cohorts 15,17,25‐30 . Studies were conducted in the United States ( n = 13) 13,15,17,19‐22,25‐30 and the United Kingdom (UK) ( n = 3) 14,23,24 and based on nine different data sources including: Massachusetts Pregnancy to Early Life Longitudinal data system (PELL, n = 3) 25‐27 ; California birth certificate and hospital discharge records ( n = 3) 15,17,29 ; Pregnancy Risk Assessment Monitoring System (PRAMS, n = 3) 13,21,22 ; and the UK National Health Service Care Quality Commission Survey ( n = 2) 14,23 . Definitions of physical disabilities varied.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with and build on a prior finding that women with complex disabilities (which include difficulty with independent living activities) were more likely to have experienced miscarriage than women without disabilities. 20 Because sporadic (as opposed to recurrent) miscarriage is not well-characterized in most women, it is difficult to determine why women with disabilities may be more likely to experience miscarriage. Other research has found that women with disabilities are more likely to have adverse preconception risk factors such as smoking, obesity, diabetes, asthma, frequent mental distress, and lack of emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…One prior study found that women with complex disabilities (those that affected activities of daily living and/or instrumental activities of daily living) were at greater risk of miscarriage than women without disabilities. 20 However, miscarriages among women with different types of disabilities (physical, cognitive, sensory ) have not yet been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Except data from small sample size studies, there are only a few population-based representative studies regarding pregnant women with overall disabilities. One study argued no difference in the risk of live births compared to non-disabled women 6 , whereas another study showed the increased risk of preterm births and LBW but not the risk of cesarean deliveries in women with disabilities 7 . Both these studies have strength in that they had a large sample size to prove the relationship, however they had limitations with regards to definition of disability, as they were based on self-reported interviews, which are subjective and unclear.…”
Section: Discussionmentioning
confidence: 99%